Sponges associated with octocorals in the Indo-Pacific, with the description of four new species - Calcinai, Barbara; Bavestrello, Giorgio; Bertolino, Marco; Pica, Daniela; Wagner, Daniel; Cerrano, Carlo (Zootaxa, 2013)
Sponges are characterised by high levels of phenotypic plasticity, thus allowing the same species to live in different habitats by taking different shapes. Here we describe 28 sponge species associated with the octocorals Carijoa riisei, Paratelesto rosea and Alertigorgia hoeksemai in Indonesia, Hawai’i and Vietnam, including four species that are new to science (Chondropsis subtilis, Hymedesmia (Hymedesmia) spinata, Hymedesmia (Stylopus) perlucida, Mycale (Aegogropila) furcata). Moreover, a large proportion of the described sponge species (21.4%) represent new records for the studied areas (Indonesia and Hawai’i). In total, we have studied 47 colonies of C. riisei associated with 24 sponge species, 5 colonies of P. rosea associated with 4 species and one colony of A. hoeksemai associated with one sponge species. Collectively, these examples of associations highlight the importance of epibiosis as a biodiversity enhancing process.